El alcance y eficacia del acta transaccional extrajudicial como título ejecutivo en el COGEP. - Moncayo Romero, Diego Sebastián (2023)
The transaction is an alternative means of effective conflict resolution, which is used by society to end its conflicts, either within a judicial process or extrajudicially, that is, without the need for a justice operator. In our legal system, since the General Organic Code of Processes came into force, extrajudicial transactions were established as an executive title, until in 2019 the reform of this code was carried out and extrajudicial transactions were simultaneously established as an enforcement title. , which gives it the effect of res judicata, finding confusion when asking the appropriate procedure to be carried out, due to the fact that the effects they generate are totally different in both titles. When analyzing the similar norm, it is necessary to compare it with other neighboring legislations, because our cultures and customs are, therefore, it was compared with the legal systems of Argentina, Peru and Colombia; in this way elucidating the effects generated by the transaction and what is the appropriate procedure to process it. At the same time, talk about the consequences in our social reality and behavior when contemplated in these two titles. In the same way when analyzing doctrine, jurisprudence, criteria, among other documents that allow specifying the transaction and giving a clear answer to the current problem of the extrajudicial transactional act, thus ending the antinomy.